Community perceptions of cooperatives: An empirical study in Costa Rica - Arzadun, Paula; Masis Solano, Paul (Cooperativismo & Desarrollo, 2020)
Introduction: While the study of the perceptions of workers in social economy organizations has been widely addressed, the same is not true of society’s perceptions of these organizations. In this sense, this article intends to shed light on how the community of the canton of San Carlos, Costa Rica, perceives cooperative companies. This canton is the largest in the entire country, and is considered the most developed and main socio-economic axis of northern Costa Rica. Additionally, it has a high relative concentration of cooperatives, which operate in almost all economic activities. Methodology: With a quantitative approach and a descriptive design, 196 surveys were conducted. Results: A community that declares itself highly knowledgeable about cooperative companies is portrayed. In terms of preferences, there are gaps between cooperative, noncooperative and public sector companies, depending on whether they are a consumer, worker or as a citizen in general perspective. Conclusions: A first approximation of the opinions of inhabitants of San Carlos was obtained regarding a subject that is scarcely explored, and completely new at the national level. Macro-trends show that cooperativism is able to forge future alternatives in the face of current challenges.